فاعلية برنامج تعليمي لتحسين مهارة القراءة لدي الأطفال ذوي صعوبات التعلم بمراكز التربية الخاصة - الشريف، أسماء عز الدين; جدي، نجدة محمد عبدالرحيم Jeddi, Najdah Mohammed Abdulrahim (جامعة السودان للعلوم والتكنولوجيا - عمادة البحث العلمى, 2016)
This study aimed to find out the effectiveness of an Instructional program to improve reading skills for children with learning difficulties in Khartoum locality. The researcher used the experimental method, one group design with a pre-post test. The research sample Consisted of (22) subjects randomly chosen. The researcher used three tools: basic information sheet, a test 22 of reading skills, and the educational program designed by the researcher. The statistical analysis was done by using the SPSS program, the important equations used were the T test and the one way ANOVA for the significance of the differences. The researcher reached results include which was the significant differences were found between the pre and post tests of the reading skills among the children with learning difficulties in favor of the post test. There were significant differences in the post test of the reading skills among the children with learning difficulties due the educational level of the mothers in favor of those with university education, whereas there were no significant differences due to the father education. There were no significant differences in the post test of the reading skills among the children with learning difficulties that due to gender and age variables. Based on these results the researcher Presented a number of recommendations and suggestions, important of which were: teachers are to be trained on the ways and means of early detection of learning difficulties among the kindergarten stage, Children Researches must be conducted on the early detection of learning difficulties among the kindergarten stage.
هدفت هذه الدراسة إلى معرفة فعالية برنامج تعليمي لتحسين مهارة القراءة للأطفال ذوي صعوبات التعلم بمراكز التربية الخاصة بمحلية الخرطوم. استخدمت الباحثة المنهج التجريبي تصميم المجموعة الواحدة مع قياس قبلي وبعدي. وتكونت عينة الدراسة من (22) طفل وطفلة تم اختيارهم بالطريقة العشوائية. تم جمع البينات عبر اختبار مهارة القراءة، من تصميم الباحثة. تمت معالجة البيانات إحصائيا باستخدام الحزم الإحصائية للعلوم الاجتماعية (SPSS) وعولجت البيانات عبر اختبار ت (T. test)، وتحليل التباين، لدلالة الفروق. وتوصلت الباحثة إلى عدد من النتائج أهمها وجود فروق ذات دلالة إحصائية بين القياسين القبلي والبعدي في مهانة القراءة لدى الأطفال ذوي صعوبات التعلم لصالح القياس البعدي. وتوجد فروق ذات دلالة إحصائية في الاختبار البعدي لمهارات القراءة لدى الأطفال ذوي صعوبات التعلم تعزى للمستوى التعليمي للأم لصالح الأمهات ذوات التعليم الجامعي بينما لم توجد فروق تعزى للمستوى التعليمي للأب. لا توجد فروق ذات دلالة إحصائية لدى الأطفال ذوي صعوبات التعلم تعزى لمتغيري النوع والعمر. وبناءاً على هذه النتائج قدمت الباحثة عدد من التوصيات والمقترحات أهمها تدريب المعلمين على طرق اكتشاف صعوبات التعلم في مرحلة مبكرة من عمر الطفل، أجراء بحوث حول الاكتشاف المبكر لذوي صعوبات التعلم في مرحلة التعليم قبل المدرسي.
Keywords: التربية الخاصة -- صعوبات التعلم -- مهارة القراءة